Social entrepreneurship in the professional training in Nursing - Backes, Dirce Stein; Colomé, Juliana Silveira; Mello, Giovana Batistella de; Gomes, Regina Celia de Castro; Lomba, Maria de Lurdes Lopes de Freitas; Ferreira, Carla Lizandra de Lima (Revista Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to assess the knowledge and practices that stimulate social entrepreneurship in the professional training of Nursing students. Methods: qualitative exploratory-descriptive study carried out with 44 Nursing students from a University in the South Region of Brazil. Data were collected between May and August 2021, through individual online interviews. The participants were students of nursing course in the 6th semester or above, who had previously participated in teaching, research, or university outreach activities on entrepreneurship. Results: the data was organized and analyzed according to the thematic analysis technique and resulted in three thematic categories: Meanings of social entrepreneurship, Factors that sparked social entrepreneurship, and Recognizing oneself as an entrepreneurial nurse. Final Considerations: the knowledge and practices that stimulate social entrepreneurship in the professional training of Nursing students are associated with teaching, research and university outreach activities that allow concrete experiences in the living and dynamic world of communities. RESUMO Objetivos: conhecer saberes e práticas que estimulam o empreendedorismo social na formação profissional de estudantes de Enfermagem. Métodos: pesquisa qualitativa de caráter exploratório-descritivo, realizada com 44 estudantes de Enfermagem de uma Universidade do Sul do Brasil. Os dados foram coletados entre maio e agosto de 2021, por meio de entrevistas individuais na modalidade online. Participaram do estudo estudantes de Enfermagem a partir do 6º semestre e que previamente haviam participado de atividades empreendedoras de ensino, pesquisa ou extensão universitária. Resultados: os dados organizados e analisados com base na técnica de análise temática resultaram em três categorias temáticas: Significados de empreendedorismo social, Experiências empreendedoras na formação do enfermeiro e Reconhecendo-se Enfermeiro empreendedor. Considerações Finais: os saberes e práticas que estimulam o empreendedorismo social na formação profissional de estudantes de Enfermagem estão relacionados às atividades de ensino, pesquisa e extensão universitárias, possibilitadas pelas vivências concretas no mundo vivo e dinâmico em comunidades. RESUMEN Objetivos: conocer los saberes y las prácticas que estimulan el emprendimiento social en la capacitación profesional de los estudiantes de Enfermería. Métodos: es una investigación cualitativa de carácter exploratorio-descriptivo, realizada entre 44 estudiantes de Enfermería de una Universidad del Sur de Brasil. Los datos se recopilaron entre mayo y agosto de 2021, mediante entrevistas individuales en línea. Participaron del estudio estudiantes de enfermería del 6º semestre que habían asistido previamente a actividades empresariales de docencia, investigación o extensión universitaria. Resultados: los datos organizados y analizados con base en la técnica de análisis temático implicaron en tres categorías: Significados del emprendimiento social, Experiencias emprendedoras en la formación del enfermero y Reconocimiento del Enfermero emprendedor. Consideraciones Finales: los saberes y las prácticas que fomentan el emprendimiento social en la formación profesional de los estudiantes de Enfermería están relacionados con las actividades universitarias de enseñanza, investigación y extensión, que se hacen posibles a través de experiencias concretas en el mundo vivo y dinámico de las comunidades.